The Ovarian Cancer Clinical Aspects and at least Two Tumor Markers for Diagnosis Laboratory Examination - Dwi Yulia; Osman Sianipar Sianipar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Ovarian cancer is one of the gynecological malignancies with a bad outcome. Epidemiologically, it is the fifth cause of death in females worldwide. Patients have various complaints, and examinations available for early detection are inadequate, causing high mortality rates and late diagnosis. Prepare a more appropriate examination to establish an earlier diagnosis, especially in females with risk factors requiring screening. Laboratory examinations combined with other supporting examinations can provide better results to confirm the diagnosis of ovarian cancer and lower the morbidity rate. Knowing the updated examination to support the diagnosis, such as examination of ovarian cancer biological markers specific to HE4, CA-125, CEA, CA 19-9. A combination of examinations is needed for early detection of ovarian cancer.